Imams al-Imam al-Bazazi (AH827) in his book al-Fatawi al-Bazazi issues purity is a model (Journal of the College of Education for Women, 2019)
The study included three topics, the definition of the personality of Imam al-Bazazi, his scientific biography, his elders, his writings, his students and his death, selected issues of his weightiness related to purity, and the Imam al-Bazazi is Muhammad ibn Muhammad ibnShihabibn Yusuf, known in al-Kardari al-Hanafi al-Balzazi. The other doctrines, the author relied in his book on the sources of the previous scholars of the Hanafis, and make them the basis in his book, the author did not adopt the definitions of language and terminology, and rarely mention the evidence Shariah adopted by scientists in their opinions, and limited to mention only opinions, In front of the first issue spotlessly water user, and the second issue that sleep lay invalidate ablution, and the third issue was likely Imam passport survey on Turkish Ixodes.